2017
DOI: 10.1007/s10899-017-9694-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gambling Activities and Gambling Problems Among Italian High School Students: Results from a Latent Class Analysis

Abstract: This study aims to provide an estimate of the prevalence of gambling among Italian adolescents and a description of their patterns of gambling activities (PGAs) using a latent class analysis on 13 different types of games. A nationwide sample of 10,959 Italian high school students was recruited in 2013. We assessed problem gambling using the South Oaks Gambling Screen: Revisited for Adolescent (SOGS-RA) scale. Approximately half (50.6%) of students reported gambling at least once in the previous year; 5.0% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…Gambling activities of out-of-school adolescents were classified into three subgroups (RG, IGG, and BG), whereas prior studies classified their subjects into 4~8 subgroups [8,14,19,20]. This result is consistent with the findings of a prior study on early adulthood gambling, which delineated three subgroups of social gamblers, problem gamblers, and pathological gamblers [21].…”
Section: Discussionsupporting
confidence: 78%
“…Gambling activities of out-of-school adolescents were classified into three subgroups (RG, IGG, and BG), whereas prior studies classified their subjects into 4~8 subgroups [8,14,19,20]. This result is consistent with the findings of a prior study on early adulthood gambling, which delineated three subgroups of social gamblers, problem gamblers, and pathological gamblers [21].…”
Section: Discussionsupporting
confidence: 78%
“…Calado and Griffiths showed in a review that all national surveys concluded that there were more gamblers than non-gamblers 1) ; for example, 75% of males and 71% of females had gambled in the previous year in the UK 2) , and 74% of the general population in France had gambled in the previous year 3) . Social gambling defined as gambling without loss of control and without damages, may become a pathological gambling in a minority of cases 4,5) . Pathological gambling is a behavioral addiction first characterized in the DSM-IV by a loss of control over gambling which then becomes the subject's only interest, prevailing over all her or his other activities, causing serious harmful consequences to social, family, or financial life.…”
Section: Introductionmentioning
confidence: 99%
“…Problem gambling (PG) is more likely to occur among men [1][2][3]8) , with psychiatric disorders 8) , or individuals of extreme age [9][10][11][12] . Environmental factors, such as level of income, socio-economic integration, or social support and working status have an influence, both on PG prevalence worldwide and on an individual's gambling trajectory between social gambling and GD 1,4,8) . Income is more associated to engagement with gambling rather than problem gambling 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Social gambling may become a gambling disorder (GD) in a minority of cases 7 8. GD is defined as a persistent, maladaptive pattern of gambling resulting in clinically significant impairment or distress, according to the Fifth Edition of the Diagnostic and Statistical Manual of Mental Disorders 9.…”
Section: Introductionmentioning
confidence: 99%
“…Problem gambling is more likely to occur among men,1 2 11 12 individuals with psychiatric disorders (anxiety, depression and attention deficit/hyperactivity disorder (ADHD)),11 or individuals of extreme old or young age 13–16. Environmental factors such as level of income, socioeconomic integration or social support have an influence both on problem gambling prevalence worldwide and on individual gambling development and transitions between social gambling and problem gambling 1 8 11. Different clusters of problem gamblers emerged through the analysis of these clinical variables 17–21.…”
Section: Introductionmentioning
confidence: 99%